Clarity and confidence : Observability on the New York Times games team - McCleary, Darren (O'Reilly Media, Inc., 2019)
The mantra with Git is "commit early, commit often." With deep insight into your applications, you can deploy early and deploy often. Darren McCleary explores how the New York Times games team fearlessly pushes changes to production and monitors its impact for 400,000+ crossword subscribers and how the team rapidly drills into issues when they occur. Topics include: How the New York Times defines observability How the New York Times has organized its infrastructure to make systems both simple and easy to monitor How to use Google Stackdriver for monitoring, logging, alerting, and distributed tracing How log metrics work and when to use them (and when not to) How to fix production issues from the bar.